Iowa Birdline update, April 4, 1994 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1994)
Email for the Iowa Birdline update for April 4, 1994. Highlights include Smith's Longspur, Sandhill Crane and Varied Thrush. Includes hand written notes in preparation for next week's update. Epson - sheet feed/flatbed